2018
DOI: 10.1186/s12886-018-0807-1
|View full text |Cite
|
Sign up to set email alerts
|

Conbercept for patients with age-related macular degeneration: a systematic review

Abstract: BackgroundConbercept is a novel vascular endothelial growth factor (VEGF) inhibitor for the treatment of wet age-related macular degeneration (AMD). This systematic review aims to assess the efficacy and safety of conbercept in the treatment of wet AMD.MethodsPubMed, Embase, Cochrane Library, China National Knowledge Infrastructure, VIP database, and Wanfang database were searched from their earliest records to June 2017. We included randomized controlled trials (RCTs) evaluating the efficacy and safety of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 21 publications
1
41
1
Order By: Relevance
“…Previous meta-analyses in nAMD had stated that conbercept was more efficacious and safer compared with ranibizumab when neglecting treatment frequency. 4,47,48 Whereas conbercept quarterly was significantly inferior in terms of efficacy to all types of ranibizumab regimen except ranibizumab quarterly regimen in our NMA. The evidence mentioned previously can also be found in mean BCVA change.…”
Section: Discussionmentioning
confidence: 65%
“…Previous meta-analyses in nAMD had stated that conbercept was more efficacious and safer compared with ranibizumab when neglecting treatment frequency. 4,47,48 Whereas conbercept quarterly was significantly inferior in terms of efficacy to all types of ranibizumab regimen except ranibizumab quarterly regimen in our NMA. The evidence mentioned previously can also be found in mean BCVA change.…”
Section: Discussionmentioning
confidence: 65%
“…Aflibercept, ranibizumab, and pegaptanib-injection product labeling and other literature discuss techniques of intravitreal injection. 181,207,[239][240][241] Recently, conbercept has shown promising results in the management of wet AMD, 242 although it has yet to receive FDA approval for its use. Similarly, abicipar has completed phase II clinical trials and has shown an extended duration of effect with a good safety profile; however, it has not received FDA approval.…”
Section: Difficulties In Dark Adaptationmentioning
confidence: 99%
“…17 Previous studies have shown that conbercept can improve a variety of clinical symptoms, such as best corrected visual acuity (BCVA), central foveal thickness (CFT), and choroidal neovascularization area. 18 Conbercept has been used in the treatment of diabetic macular edema, 17 wet age-related macular degeneration, 19 chronic central serous chorioretinopathy, 20 and proliferative diabetic retinopathy. 14 However, conbercept has not been reported as a common treatment for NPDR.…”
Section: Introductionmentioning
confidence: 99%